Vận dụng mô hình CIPO trong quản lí đào tạo lí luận chính trị tại các trường chính trị theo tiếp cận năng lực - Trần Bá Long, Trần Bá Long; Cao Danh Chính, Cao Danh Chính (Tạp chí Giáo dục, 2026)
In the context of organizing and operating local government under a two-tier model, political theory education is required to shift from knowledge transmission toward developing the capacity to apply theoretical foundations in practical cadre-related tasks. However, practices at political schools indicate that the implementation of competency-based education remains limited, primarily due to fragmented training management and a lack of systemic coherence and alignment among context, objectives, instructional processes, and training outcomes. This article analyzes the “Context - Input - Process - Output” (CIPO) model as a framework for competency-based training management in political theory education. Based on a theoretical review, document analysis, and expert consultation, the study constructs an analytical framework for applying the CIPO model from a systems perspective, in which the competency-based approach guides training objectives and learning outcome standards. The research findings demonstrate that applying the CIPO model helps restructure the logic of training management in a systemic manner, ensuring coherence and feedback mechanisms among its components, with learning outcomes - reflected in trainees’ task performance competencies -serving as the central element. The study clarifies the operational mechanism of competency-based training management and provides a scientific foundation for improving the effectiveness of political theory education in the current context.